Emergency Service Response Time Performance Analysis in the Hospitals with Level Two Health Facilities: Comparative Study - Lidiana, Exda Hanung; Pratiwi, Arum; Sugiharto (Universitas Muhammadiyah Surakarta, 2024)
The Emergency Unit (ER) is a part of the hospital that provides rapid treatment for patients according to the severity of their condition. Response time is the speed of the medical team in the ER in treating patients, starting from the moment the patient arrives until medical action is given. Fast and precise response time can reduce the complications that can arise and the patient's cost burden. The number of patients and the number of nurses that are not comparable can affect the response time of nurses. Research observing and comparing response times is still very limited. This study aims to determine the difference in service response time in the ER in two hospitals with second-level health facilities. This type of research is quantitative using a descriptive comparative approach. The research method uses observation and questionnaire methods. Data collection directly using the stopwhatt tool. Sampling was taken using the Accidental sampling technique. Data analysis used the difference between two means test with Mann-Whitney. Observations were carried out on nurses in the emergency room totaling 52 observations in each hospital for three months. The results of the analysis show a value of P = 0.688, where this probability value is more than 0.05, so the hypothesis fails to be rejected, so it can be concluded that statistically there is no significant difference in the Response Time of nurses in the two Emergency Units. Nurses must provide a response time according to the regulations set by the Ministry of Health, namely less than five minutes.